Acne and diet: dairy products fats and carbohydrates (Eurasian Medical Research Periodical, 2023)
This article delves into the intricate connection between diet and acne, focusing on the potential influence of dairy products, fats, and carbohydrates. Through a comprehensive literature analysis, the study explores existing research to understand the methods employed, results obtained, and the subsequent discussions. The goal is to provide valuable insights into the complex interplay between dietary choices and skin health, offering readers a nuanced perspective on managing acne through nutritional considerations